HIZB UT-TAHRIR`S FIGHT BACK: THE RESPONSES OF HIZB UT-TAHRIR INDONESIA TO THE STATE REPRESSION - Hasbi Aswar; Danial Bin Mohd. Yusof; Rohana Binti Abdul Hamid (Jisiera: The Journal of Islamic Studies and International Relations, 2020)
Islamic political movements in the world politics are mostly responded by the state through repressive policies. Those groups are banned; their members are arrested, and even killed. Hizb ut-Tahrir is one example of an Islamic political movement that has gone through many kinds of state repression. In Indonesia, even though this group has for a long time enjoyed an open political space to work, it changed significantly after the state issued a policy to resolve this movement in Indonesia. This article aims to discuss the impact of the state policy to hizb ut-tahrir Indonesia by using a social movement approach on the impact of state repression to social movement. This paper argues that HTI responds to state policy by countering the state policy through political and legal strategy.